Lymphocyte apoptosis and apoptosis?associated gene expression in Sjögren's syndrome (1996)
Objective . To study the mechanism and regulation of apoptosis in peripheral blood T and B lymphocytes from patients with Sjögren's syndrome (SS). Methods . The mode of in vitro lymphocyte death in the peripheral blood of patients with SS was determined by fluorescence microscopic analysis, terminal deoxynucleotidyl transferase assay, and DNA fragmentation analysis. Apoptotic cell death of T and B cells was determined at 48 hours of culture by fluorescence?activated cell sorter analysis of propidium iodidestained cells. Messenger RNA (mRNA) expression of bcl?2, bcl?x, bax , and c?myc in T and B cells was determined by enzyme?linked immunosorbent assaypolymerase chain reaction (ELISA?PCR). Expression of bcl?xL and bcl?xS was determined by Southern blot analysis of PCR products. Gene expression was calculated as the ratio of each gene message to the message of the GAPDH gene. Bcl?2 protein levels in SS T cells were determined by ELISA. Results . SS T cells showed increased in vitro apoptosis compared with normal T cells (mean ± SD 12.3 ± 4.5% versus 7.3 ± 2.0%; P < 0.01). Freshly isolated SS T cells showed increased expression of bcl?2 mRNA compared with normal controls (mean ± SD 1.50 ± 0.65 versus 0.88 ± 0.23; P < 0.05). There was no significant difference in levels of bax or c?myc mRNA in T cells and B cells between SS patients and normal controls. When SS T lymphocytes were cultured in vitro for 72 hours, Bcl?2 protein levels decreased with time. Conclusion . SS T cells showed accelerated apoptosis in vitro. Freshly isolated SS T cells had increased expression of bcl?2. An increase in death?promoter signals and decrease in death?suppressor signals in vitro may have been responsible, in part, for the apoptosis in SS T lymphocytes.